2007 ICTON Mediterranean Winter Conference 2007
DOI: 10.1109/ictonmw.2007.4446920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymer host on third order nonlinear optical properties of newly synthesized organic liquid crystal

Abstract: We report the investigation of third order optical nonlinearity of 2,4,6-tri-(p-hyptoyoxylphenyl) pyrilium tetraborate doped PMMA using nanosecond laser pulses at 532nm wavelength by employing Z-Scan technique. To see the effect of polymer host, the results have been compared with the pure dopant. The material shows a large negative nonlinearity with real and imaginary parts of χ (3) are -3.31x10 -14 esu and 0.73x10 -14 esu respectively. Excited state absorption cross-section is found to be 3.41x10 -48 cm 4 .s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The results showed that the nonlinear refractive index in the film was 300 times larger than that in solution. Compared with many other organic materials, such as DDLC, 21 Sudan I, 22 and some organic D‐π‐A compounds, 13 the nonlinear refractive index in LCP was larger. The good nonlinear response of this material indicates it has potential applications in optical devices such as all‐optical switches and modulators.…”
Section: Resultsmentioning
confidence: 92%
“…The results showed that the nonlinear refractive index in the film was 300 times larger than that in solution. Compared with many other organic materials, such as DDLC, 21 Sudan I, 22 and some organic D‐π‐A compounds, 13 the nonlinear refractive index in LCP was larger. The good nonlinear response of this material indicates it has potential applications in optical devices such as all‐optical switches and modulators.…”
Section: Resultsmentioning
confidence: 92%